DRIVERS AND RESERVES OF LABOR PRODUCTIVITY GROWTH IN SMALL BUSINESS ENTERPRISES (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article examines the key drivers and internal reserves of labor productivity growth in small business enterprises, with a focus on economic, organizational, and institutional factors shaping productivity dynamics. The study analyzes how human capital quality, technological adoption, managerial practices, and resource allocation influence productivity performance in small firms. Particular attention is paid to the identification of underutilized reserves, including organizational efficiency, workforce skills development, digitalization, and innovation capacity. The research highlights that labor productivity growth in small businesses is determined not only by external market conditions, but also by the ability of enterprises to mobilize internal potential and adapt to structural changes. The findings emphasize the importance of targeted policy measures and enterprise-level strategies aimed at enhancing productivity through the effective use of available resources and development opportunities. The article contributes to the literature on small business economics by providing a structured framework for analyzing productivity drivers and by offering practical insights for improving the competitiveness and sustainability of small business enterprises.